MEMBANGUN DESA MANDIRI ENERGI MELALUI PENGOLAHAN SAMPAH PLASTIK MENJADI BBM ALTERNATIF DI DESA HANURA KECAMATAN TELUK PANDAN PESAWARAN - Bahri, Syaiful; Ambarwati, Yuli; Waluyo, Sri; Oktarina, Rasmi Zakiah; Notiragayu, Notiragayu (Jurnal Abdi Insani, 2024)
The market in Hanura Village faces serious problems related to rubbish, especially because it is located close to the main beach tourist route which is busy during holidays. Increased activity in markets produces more waste, which is usually simply transferred to landfill, but this method is less effective. Plastic waste is the second biggest problem after organic waste and is difficult to decompose naturally, so other solutions are needed to reduce waste accumulation. To tackle this issue, the Unila community service team proposes a more efficient plastic waste management system. Drawing from Bahri et al., (2019), their research demonstrates that plastic waste can be converted into alternative fuel through a pyrolysis process, utilizing a device known as a pyrolizers. With an abundant supply of plastic waste and Hanura Village’s strategic location, the development and application of this process are being implemented through a community service program based on research dissemination. The result of this activity is a plastic waste processing tool that converts waste into alternative fuel in the form of a pyrolyzer with three condensers. The fuel produced from the pyrolysis of plastic waste is characterized by its chromatogram profile using Gas Chromatography Mass Spectrometry (GCMS), and its calorific value is measured using a bomb calorimeter, while the octane number is determined using an Octane Number Tester.  The results of the community service activity in Hanura Village cognitively show that the residents of Hanura Village were highly enthusiastic about receiving the training, especially related to the processing of plastic waste into fuel, with an overall achievement of specific instructional objectives reaching 53%.